Factors contributing to successful trauma registry implementation in low- and middle-income countries: A systematic review. Issue 12 (December 2018) - St-Louis, Etienne; Paradis, Tiffany; Landry, Tara; Poenaru, Dan
Abstract: Background: Trauma registries (TR) provide invaluable data, informing resource allocation and quality improvement. The purpose of this systematic review was to identify factors promoting and inhibiting successful TR implementation in low- and middle-income countries (LMICs). Methods: The protocol was registered a priori (CRD42017058586). With librarian oversight, a peer-reviewed search strategy was developed. Adhering to PRISMA guidelines, two independent reviewers performed first-screen and full-text screening. Studies describing implementation of a TR in LMICs or reviewed the experience of registry users/implementers were included. Extracted data, focusing on publication, institution, registry and data factors, was summarized using descriptive statistics and subjected to thematic qualitative analysis. Results: Out of 3842 screened references, 40 articles were included for analysis. Most registries were paper-based, implemented in single publicly-funded institutions within LMICs, benefited from funding, and were run by untrained house-staff with other clinical responsibilities. Constituent variables, injury scoring, outcome assessment, and quality assurance practices were very diverse. Principal obstacles to successful implementation were lack of funding, significant missing data, and insufficient resources. Conclusions: This work may contribute to the planning of future efforts towards TR implementation in LMICs, where better injury data has the potential to alleviate the morbidity and mortality associated with trauma through advocacy and quality-improvement.